ИНДУКЦИЯ КАЛЛУСООБРАЗОВАНИЯ И РЕГЕНЕРАЦИИ ИЗ ЗРЕЛЫХ ЗАРОДЫШЕЙ КАЗАХСТАНСКИХ СОРТОВ РИСА (Experimental biology, 2015)
In present paper influence of genotype and nutrient media for callus induction and plant revering from mature embryo culture of rice is shown
Keywords: embryo culture of rice